2016
DOI: 10.1016/j.repbio.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Differential influence of ampullary and isthmic derived epithelial cells on zona pellucida hardening and in vitro fertilization in ovine

Abstract: The central role of the oviduct, as the site of zona pellucida (ZP) maturation, fertilization and early embryogenesis, has been recognized. The objective of this study was to investigate whether ampullary and isthmic derived epithelial cells have different effects on in vitro ZP hardening, in vitro fertilization (IVF) and in vitro culture (IVC) of the resulting embryos. Cumulus oocyte complexes (COCs) were matured in a coculture system with ampullary/isthmic epithelial cells, TCM199 supplemented with insulin-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Additionally, OECs-provided maintenance of embryonal growth was associated with synthesis of various growth factors [25]. Therefore, it is assumed that OECs are programmed to support fertilization and further embryo development [32].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, OECs-provided maintenance of embryonal growth was associated with synthesis of various growth factors [25]. Therefore, it is assumed that OECs are programmed to support fertilization and further embryo development [32].…”
Section: Discussionmentioning
confidence: 99%
“…Another difference between IVF and in vivo fertilization is the zona pellucida hardening and monospermy during fertilization (Mondejar et al 2013, Anifandis et al 2016, Dadashpour Davachi et al 2016. In a natural pregnancy, the female reproductive tract acts as a passage for sperm selection, by which it minimizes the number of sperm reaching the fertilization site to ensure that polyspermy occurs at a low rate.…”
Section: Developmental Factors Missing In Vitromentioning
confidence: 99%
“…To overcome this, one could use a co-culture condition of the egg and oviduct epithelia. An experiment demonstrated that co-culture of eggs and oviductal epithelial cells is significantly better at preventing polyspermic fertilization than the standard IVF counterpart (Dadashpour Davachi et al 2016). This suggests that fertilization in the oviduct is part of a continuing interaction between gametes and oviduct to optimize the fertilization outcome.…”
Section: Developmental Factors Missing In Vitromentioning
confidence: 99%
“…After crossing the utero-tubal junction, a sub-population of sperm [ 60–65 ] is able to bind to OECs of the isthmus, forming a sperm reservoir [ 12 , 17 , 18 , 41 , 67 ], and also of the ampulla close to the fertilization site [ 32 , 34 , 56–58 ]. Binding to OECs maintains sperm viability [ 34 , 41 , 64 , 67–70 ], membrane, and acrosome integrity [ 57 , 60 , 61 , 64 ] and increases the rates of oocyte penetration and monospermy in vitro [ 68 , 73–75 ] especially in the ampulla [ 112 ]. Subsequent release of spermatozoa from OECs induced sperm capacitation and hyperactive motility [ 74 , 104–106 , 109 ].…”
Section: Spermatozoa Bind To Oviduct Epithelial Cells In the Sperm Reservoirmentioning
confidence: 99%
“…Moreover, for the optimization of cryopreservation media in cattle, the addition of proteins from OECs apical membrane was shown to better maintain post-thaw sperm membrane integrity when using isthmic rather than ampullary cells [ 111 ]. In sheep, the penetration of oocytes and monospermic fertilization were promoted by the addition of ampullary but not isthmic OECs to the fertilization medium [ 112 ]. Taken together, these data indicate that at least in ruminants, the micro-environment of the ampulla may be more capacitating, whereas that of the isthmus may be more conducive to sperm survival.…”
Section: Regions Of the Oviduct Play Different Roles In Regulating Sperm Physiology And Interactions With Oecsmentioning
confidence: 99%